Strut Adjusted Volume Implant(SAVI) - An Interim Report of Patient Satisfaction and Outcomes - Yamamoto, Daigo; Siga, Toshiko; Yoshikawa, Katsuhiro; Tsubota, Yu; Sueoka, Noriko; Chiba, Tsukuru; Ishizuka, Mariko; Kon, Masanori (Gan to kagaku ryoho, 2017)
Strut adjusted volume implant(SAVI)was approved by the Food and Drug Administration(FDA)for the treatment of breast cancer in 2006. The phase II study was conducted to investigate the activity and safety of SAVI in breast cancer patients. Criteria for SAVI treatments were N0, T<2 cm, and age≥40. After patients underwent breast-conserving surgery, they received SAVI twice a day×5 days(34 Gy). The primary endpoint are feasibility and safety. Second endpoint are local recurrence rate and cosmesis. Three patients were enrolled and the median duration of administration is 18.7 days(17-20). Further, the most common treatment-related adverse events were thickening and redness of skin(grade 1/2), while there was no deformity of breast in each case. The current study demonstrated that SAVI is well tolerated treatment in breast cancer patients and may be convenient for use in patient treatment.